APPRAISAL: RADAR FOR CATCHING MEANING AN ANALYSIS OF MICHAEL JACKSON’S ‘EARTH SONG’, ‘WE ARE THE WORLD’, AND ‘HEAL THE WORLD’ (Universitas Negeri Semarang, 2012)
Appraisal System (system penaksiran) adalah sebuah system dari interpersonal meaning. Dalam kehidupan sehari-harinya interpersonal meaning berperan sebagai alat bagi masyarakat untuk menegosiasikan sikap dan perasaan mereka. Maka dari itu, kejadian-kejadian social akan menghasilkan teks dimana itu tertulis atau lisan. Dari poin tersebut lirik lagu didefinisikan sebagai teks yang menegosiasikan tingkah laku dan perasaan terhadap pendengarnya. Studi ini ditujukan untuk menggambarkan alat penafsiran pada lirik lagu dengan mengikuti system penafsiran Martn dan Rose (2003). Metode yang digunakan dalam penelitian ini adalah deskriptif qualitative. 3 lirik lagu adala data dari penelitian ini. Teknik analisa menggunakan alat penafsir. Hasil menunjukan bahwa pada lirik lagu ‘Earth’ ditemukan 35 unsur penggugah, 11 penilaian, dan 10 apresiasi. Pada lagu ‘heal’ terdapat 18 unsur penggugah, 22 penilaian, dan 9 apresiasi. Sedangkan pada lagu ‘ We Are The World’ terdapat 16 unsur penggugah, 18 penilaian, dan 12 apresiasi. Selain itu, diantara 56 potongan lirik pada lagu ‘Earth’ didominasi oleh penggunaan system penaksiran (62,50%) diikuti judgement (19,64%), dan apresiasi (17,86%). Pada saat yang sama diantara 48 potongan lirik ‘Heal The World’; apresiasi kurang dari proporsi pada penggunaan appraisal system (18,37%). Aspek pengaruh memiliki proporsi yang lebih besar (36,73%) dan aspek penuilaian adalah yang paling besar dari semua (44,9%). Diantara 46 potongan lirik ‘We Are The World’ memiliki proporsi yang sama dan tidak ada dominasi oleh aspek tertentu dengan perincian 39,13% untuk aspek penilaian, 34,78% pada aspek pengaruh, dan 26,1% pada aspek apresiasiAppraisal is a system of interpersonal meanings. In social relationship with others, interpersonal meaning acts as a tool for people to negotiate their attitudes and feelings. Therefore, every social event that appears is social relationship that results in a text that might be spoken or written. From this standpoint, song lyric is a kind of text through which the lyricist negotiates his or her attitudes and feelings with the listeners. This study intends to describe appraisal devices that occurred in the song lyric, to analyze the appraisal device implied in the song lyric by following the system network of appraisal offered by Martin and Rose (2003). The research method used in this study is qualitative descriptive in nature. The 3 song lyrics are, therefore, the data under analysis in this thesis. Since appraisals in written texts concern with the choice of words as devices to realize people’s attitudes and feeling, the unit of analysis in this study is appraisal device. The result of the study shows that in the lyric of earth song, it is found that there are 35 instances realizing affects, 11 judgments, and 10 appreciations. Meanwhile, in the song of heal the world there are 18 instances realizing affects, 22 judgments, and 9 appreciations. Whereas, in we are the world, there are 16 instances realizing affects, 18 judgments, and 12 appreciations. Moreover, among 56 chunks in earth song lyric, affect dominates the use of appraisal system (62, 50%) followed by judgment (19, 64%), and appreciation 17, 86%). In the meantime among 49 chunks in heal the world lyric; appreciation has less proportion of the use of appraisal system (18, 37%). Affect has bigger proportion of it (36, 73%). And judgment is the biggest of all (44, 9%). Then, among 46 chunks of we are the world lyric, this time the percentage of proportion of each of the three kinds of attitudes employed by the lyricist has relatively equal proportion. There is no domination among three of attitudes. But still judgment is in the first place with 39, 13%. Affect is in the second place with 34, 78%, and appreciation is in the last place with 26, 1%.